Thermal Effects on the Mechanical Performance of Adhesively Bonded T-Joints for Structural Applications to Support Sustainable Development Goals (SDGs) - Mohd Afendi Bin Rojan; Izzawati Basirom; Mohd Shukry Abdul Majid; Ruslizam Daud; Abu Bakar Shahriman (ASEAN Journal for Science and Engineering in Materials, 2026)
This study investigates the thermal effects on the mechanical performance of adhesively bonded T-joints, with a focus on optimizing bond strength under elevated temperatures. Using tensile testing, four adhesive thicknesses (0.5, 1.0, 1.5, and 2.0 mm) were examined across five temperatures (room temperature to 100°C). Results reveal that tensile strength peaked at 35°C, aligning with the adhesive's glass transition temperature (Tg), with 1.5 mm thickness yielding optimal performance. Thicker bonds (2.0 mm) exhibited superior strength at higher temperatures (55–100°C), while thinner bonds performed best at lower temperatures. Differential Scanning Calorimetry and SEM analyses confirmed thermal degradation and morphological changes as key factors influencing strength. These findings highlight the relationship between adhesive thickness, thermal exposure, and structural integrity, providing critical insights for the aerospace and automotive industries. The study aligns with SDG 9 (Industry, Innovation, and Infrastructure) by supporting durable design practices and contributes to the bibliometric discourse on epoxy-based adhesive technologies under thermal stress.